Statistical performance assessment of supervised machine learning algorithms for intrusion detection system - Afolabi, Hassan A.; Aburas, Abdurazzag A. (Institute of Advanced Engineering and Science, 2024)
Several studies have shown that an ensemble classifier's effectiveness is directly correlated with the diversity of its members. However, the algorithms used to build the base learners are one of the issues encountered when using a stacking ensemble. Given the number of options, choosing the best ones might be challenging. In this study, we selected some of the most extensively applied supervised machine learning algorithms and performed a performance evaluation in terms of well-known metrics and validation methods using two internet of things (IoT) intrusion detection datasets, namely network-based anomaly internet of things (N-BaIoT) and internet of things intrusion detection dataset (IoTID20). Friedman and Dunn's tests are used to statistically examine the significant differences between the classifier groups. The goal of this study is to encourage security researchers to develop an intrusion detection system (IDS) using ensemble learning and to propose an appropriate method for selecting diverse base classifiers for a stacking-type ensemble. The performance results indicate that adaptive boosting, and gradient boosting (GB), gradient boosting machines (GBM), light gradient boosting machines (LGBM), extreme gradient boosting (XGB) and deep neural network (DNN) classifiers exhibit better trade-off between the performance parameters and classification time making them ideal choices for developing anomaly-based IDSs.